2001
DOI: 10.1100/tsw.2001.265
|View full text |Cite
|
Sign up to set email alerts
|

Using Milk Urea Nitrogen to Evaluate Diet Formulation and Environmental Impact on Dairy Farms

Abstract: Reducing nitrogen (N) excretion by dairy cattle is the most effective means to reduce N losses (runoff, volatilization, and leaching) from dairy farms. The objectives of this review are to examine the use of milk urea nitrogen (MUN) to measure N excretion and utilization efficiency in lactating dairy cows and to examine impacts of overfeeding N to dairy cows in the Chesapeake Bay drainage basin. A mathematical model was developed and evaluated with an independent literature data set to integrate MUN and milk c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(56 reference statements)
1
6
0
1
Order By: Relevance
“…Regression equations developed in the current study showed that urinary N output is positively related to MUN output and dietary CP content, which can be used as readily available predictors in practice. Positive relations between urine N output and MUN concentration have been found previously and explained by 8119 the small neutral nature of a urea molecule, allowing MUN to equilibrate with BUN via diffusion into and out of the mammary gland (Jonker and Kohn, 2001). Spek et al (2013) also found that urine N outputs' best sole predictors were feed CP content and MUN content.…”
Section: Development Of Regression Equations Estimating Urine N Excretion For Grazing Dairy Cowssupporting
confidence: 53%
See 1 more Smart Citation
“…Regression equations developed in the current study showed that urinary N output is positively related to MUN output and dietary CP content, which can be used as readily available predictors in practice. Positive relations between urine N output and MUN concentration have been found previously and explained by 8119 the small neutral nature of a urea molecule, allowing MUN to equilibrate with BUN via diffusion into and out of the mammary gland (Jonker and Kohn, 2001). Spek et al (2013) also found that urine N outputs' best sole predictors were feed CP content and MUN content.…”
Section: Development Of Regression Equations Estimating Urine N Excretion For Grazing Dairy Cowssupporting
confidence: 53%
“…Previous work has shown that MUN concentration and urine N output are positively associated with dietary CP level, most likely a result of increased BUN (Jonker and Kohn, 2001;Huhtanen et al, 2015); therefore, MUN has been suggested as a noninvasive indicator for urine N excretion (Jonker and Kohn, 2001). Concentration of MUN is highly related to dietary CP content, and measurement is common practice in the dairy industry.…”
Section: Development Of Regression Equations Estimating Urine N Excretion For Grazing Dairy Cowsmentioning
confidence: 99%
“…Measurements of milk urea nitrogen can be utilized as a diagnostic of N excretion and utilization efficiency in lactating dairy cows, and has a negative non-linear correlation with milk protein content (Jonker and Kohn, 2001). Moreover, excretion of excess urea is an energy requiring process, and properly reducing of milk urea nitrogen can increase milk production (Garcia et al, 1997).…”
Section: Feeding Behaviors Between Divergent Rfi Groupsmentioning
confidence: 99%
“…Analizar los componentes de la leche resulta sencillo y, de una manera alternativa, permite evaluar la nutrición y la detección rápida de desbalances en la dieta y desórdenes metabólicos subclínicos (Jonker & Kohn 2001;Eicher 2004).…”
Section: Discussionunclassified